The contributing role of CCR5 in dementia - Zheng, Tong; Ye, Meiping; Zhou, Pingyu (Frontiers in Neurology, 2025)
Dementia is a syndrome of impaired brain function in which cognitive functions such as memory, language, attention, direction, and judgment are impaired, affecting or interfering with daily functioning. As dementia becomes more widespread, it is crucial to investigate the underlying mechanisms that contribute to cognitive decline. C-C chemokine receptor 5 (CCR5) has been extensively researched for its role in immune responses and function as a co-receptor in HIV infection. Current research indicates that CCR5, which acts as a regulator of synaptic plasticity, is involved in modulating various forms of learning and memory. Most studies suggest that CCR5 generally has a detrimental effect on diseases associated with dementia. This review seeks to deliver an extensive analysis of CCR5’s role in cognitive processes by summarizing existing literature from both animal and human studies. It will cover the involvement of CCR5 in standard learning and memory functions, as well as in various types of dementia. The review will specifically address conditions such as HIV-related neurocognitive impairment (HAND), Alzheimer’s disease (AD), stroke, vascular dementia, multiple sclerosis (MS), frontotemporal dementia (FTD), dementia with Lewy bodies (DLB), and Parkinson’s disease with dementia (PDD). Based on the fact that CCR5 plays a contributing role in many diseases that cause dementia, this review also proposed CCR5 inhibition as a possible target for alleviating and ameliorating dementia.